Investigating the effect of incident intensity on single-junction GaAs PV cells conversion efficiency at different temperatures - Junyue Zhang; Shunhua Wu; Jiachen Liu; Weizhou Huang; Lei Ling; Qingkai Meng; Rui Zhang; Lang Chen; Jiachen Zhang; Zhenfu Wang; Te Li (Materials Research Express)
Laser Power Transmission is emerging as a highly promising method for wireless energy transfer, particularly for extending the operational endurance of small unmanned aerial vehicles and supporting the construction of space-based solar power stations. This study investigated the optimal operational parameters of single-junction gallium arsenide (GaAs) photovoltaic (PV) cells under laser diode irradiation to enhance the efficiency of LPT systems. A detailed theoretical analysis was conducted to examine the effects of incident light intensity and spot size on the photoelectric conversion efficiency of GaAs PV cells across different temperature ranges. Experimental results demonstrated that as the temperature decreases from 55 °C to 5 °C, the incident intensity required for the photovoltaic cells to achieve peak efficiency rises from 0.35 W cm ^−2 to 0.65 W cm ^−2 . Consequently, higher incident intensities are necessary for optimal efficiency when PV cells operate at lower temperatures. The 2 cm photovoltaic cells can attain a conversion efficiency exceeding 50% only when exposed to a 2 cm incident light spot. Therefore, high efficiency in photovoltaic cells is attainable solely when the size of the incident light spot is as closely matched to the cell’s size as possible. Additionally, this study provides an in-depth discussion of factors limiting photoelectric conversion efficiency and the underlying mechanisms at various temperature conditions.